Artificial intelligence in Industry 4.0: Implications for occupational safety and health - Pierre Bérastégui (European Trade Union Institute (ETUI), 2024)
Artificial intelligence (AI) has long been hailed as a transformative force set to revolutionise various aspects of our lives, including the way we work. Advances in complementary fields such as big data, cloud computing and the internet of-things have seen the emergence of new ways of organising the means of production. Behind these new ecosystems, often referred to using '4.0' terms, lies a complex web of intricate technologies, bringing with it a unique set of risks and challenges. This working paper analyses the role of AI in the context of Industry 4.0 (I4.0), with a specific focus on occupational safety and health (OSH) implications. Section 1 situates AI within the framework of I4.0 and provides a brief overview of application-pull and technology-push factors inducing a need for changes. Section 2 delves into ways in which an AI system may unexpectedly fail and discusses trends in AI accidents based on available data. Section 3 explains how the growing convergence of information and operational technology make organisations more vulnerable to cyber-physical attacks, ultimately putting workers' safety at risk. Section 4 provides a critical assessment of the various principles put forward to ensure proper human oversight. Section 5 discusses how the implementation of AI systems may influence workers' autonomy and, in this way, compromise workers' safety and health. Finally, Section 6 describes the poor working conditions of data workers behind AI systems.
Keywords: 330; Artificial intelligence; Industry 4.0; occupational safety and health